Загрязнение муниципальных вод фармацевтическими препаратами и их производными - Самойленко, Наталья Николаевна; Ермакович, Ирина Анатольевна (Технологический центр, Украинский государственный университет железнодорожного транспорта, 2013)
Показана актуальность проблемы загрязнения муниципальных сточных и природных вод фармацевтическими препаратами и их производными. На примере образования стоков клинической больницы в городе Харькове (Украина), предлагается способ расчета концентраций наиболее распространенных фармацевтических загрязнителей, поступающих в них в результате выведения лекарства из организма больного.

Water pollution by pharmaceutical products (FP) and their derivatives is observed in many countries around the world and has a tendency to globalization. Therefore, it is necessary to conduct the researches, aimed at investigating pollution sources and determining their quantity in effluents. an alternative of instrumental measuring of concentrations of these substances in effluent and surface waters is their theoretical calculating. The paper proposes a method for calculating the concentration of the most commonly used FP, getting to effluent waters of hospitals, as well as to effluent waters formed as a result of transient treatment of patients in residential areas. The proposed approach of quantitative determination of pollutants can be used as a tool for screening and monitoring of effluent and surface waters as well as during consideration of project and operational issues related to sanitation and water treatment.
Municipalwaters pollution by pharmaceuticals and their derivatives
Keywords: муниципальные стоки; загрязнение; фармацевтические препараты; действующее вещество; концентрация загрязнителя; municipal effluents; pollution; pharmaceutical products; active substance; concentration of pollutant